Relatório de estágio técnico profissional em medicina veterinária: bovinocultura leiteira - Schäfer, Artur Cassolli (2023)
This instrument aims to report the activities carried out by academic Artur Cassolli Schäfer during the Professional Technical Internship (ETP), in the Veterinary Medicine activity, carried out at the company Produtiva Assessoria Veterinária with headquarters in the municipalities of Cacique Doble/RS and Erechim/RS, from July 27th to November 3rd, 2023. The activities monitored were in the areas of medical clinic, surgical clinic, preventive veterinary medicine, laboratory tests, health and reproductive management, aimed at dairy cattle farming, totaling 552 hours. The handling of these animals was carried out in the field, on the respective properties, with different procedures being carried out, such as: fixed-time artificial insemination protocols (TAI), surgeries, herd vaccination and clinical care. The laboratory tests were carried out in the laboratory of the company Produtiva. The case report presented is an approach to the outbreak of respiratory disease caused by the bovine respiratory syncytial virus (BRSV) in 5 adult animals, of the Holstein breed, which occurred in the interior of the municipality of Passo Fundo/RS. Finally, the Professional Technical Internship allowed you to experience the functions of a Veterinary Doctor immersed in the area of ​​dairy cattle farming, as well as interacting with qualified professionals, providing great professional maturity, as well as the opportunity to practice and consolidate the knowledge obtained in the classroom during the period of graduation in Veterinary Medicine.